Synchronous Abdominal Wall and Small Bowel Transplantation: Critical Insights at 4-Year Follow-up - Nicholas C. Oleck; Ralph F. Erdmann; Kadiyala V. Ravindra; Debra L. Sudan; Brett T. Phillips; Suhail K. Mithani; Detlev Erdmann; Andrew Atia (Journal of Reconstructive Microsurgery Open, 2024)
This 4-year follow-up of synchronous abdominal wall vascular composite allotransplantation (AW-VCA) and small bowel transplantation reveals novel insights and innovations in abdominal wall VCA. The case, involving a 37-year-old male Army veteran, showcases the benefits of AW-VCA in addressing loss of abdominal domain in intestinal transplantation (ITx). The events leading to ultimate rejection of both the AW-VCA and small bowel graft at 4 years highlights the complex interplay between graft survival, patient compliance, and immunosuppressive management. Notably, a significant discordance between AW-VCA and ITx rejection patterns was identified, questioning the reliability of skin components in AW-VCA as early indicators of ITx rejection. Furthermore, the behavior of the vascularized abdominal fascia, observed postexcision of the small bowel graft, offers new understanding of the immunologic response to fascia-only grafts. This follow-up emphasizes the complexities of graft survival, patient compliance, and immunosuppressive management, underscoring the need for ongoing research and innovation in the field.